Export Performance as an Antecedent of Export Commitment and Marketing Strategy Adaptation: Evidence from Small and Medium Sized Exporters - Montgomery, David B. (Institutional Knowledge at Singapore Management University, 2004)
This paper argues that performance should be investigated as an independent variable. Using survey data of over 400 managers responsible for the main export ventures of Portuguese SMEs (small and medium exporters), this paper shows that past performance plays a crucial role in building SMEs' commitment to exporting and to the determination of their current marketing strategy. Findings also show that marketing strategy adaptation to the foreign market is particularly noted in firms exporting to the most developed markets, rather than in firms exporting to the most competitive environments. Future international marketing research is encouraged to focus on understanding both the direct and indirect relationships among past performance, firm's commitment to exporting, and current marketing strategy under the influence of external forces. Such a focus has the potential to enrich the theory and generate relevant managerial and public policy implications.